Analisis Pola Penyebaran Kemiskinan Di Indonesia - Indra Budiman; Fajar Restuhadi; Syaiful Hadi (Jurnal Kebijakan Pembangunan dan Inovasi, 2019)
Poverty is one of the fundamental problems that is the center of attention in development country, including in Indonesia. One of the most aspect to support poverty reduction is accurate and targeted poverty data. The purpose of this research is analyze patterns of poverty distribution based on regencies and cities in Indonesia, analyze information revealed based on patterns formed and formulate an appropriate poverty reduction strategy based on patterns formed. From the results of cluster analysis, used data from central bureau of statistics and relevant regional income and expenditure budget, consisting of 33 poverty indicators with 16,566 data cells covering 502 districts / cities in Indonesia. Determination of the sample in this research is census method. The results showed that Kaiser Meyer Olkin (KMO) value and Measures of Sampling Adequacy (MSA) > 0,5 that were worthy of further testing were 30 indicators. The results of cluster analysis formed 10 clusters consisting of 209 districts / cities with similar characteristics or patterns at correlation level >0.5. Alternative solutions for poverty alleviation strategies by looking at the main aspects of each cluster, where each cluster has different characteristics from one another based on existing patterns